Theoretical, practical and hybrid ex-academics: Career transfer stories - Päivikki Kuoppakangas; Kati Suomi; Elias Pekkola; Jussi Kivistö; Tomi Kallio; Jari Stenvall (Sage, 2022)
The academic career stories and trajectories of PhD holders have been widely studied in the context of economic austerity and an oversupply of doctors. However, few studies have investigated career building among ex-academics and how a doctoral degree and university work might affect their career possibilities outside academia. This paper explores the trajectories of ex-academics: PhDs with university work experience who have left academia to pursue non-academic careers. Based on 40 qualitative interviews with ex-academics, their employers and senior university leaders, the study employs a narrative approach to construct five career stories: the Theoretical Endangered Nerd, the Practical Geek, the Chic Hybrid, the Pristine Novice and the Odd Elite. This varied picture of career sensemaking provides new insights into career building among ex-academics.